A Tribute to Richard M. Crooks on the Occasion of His 65th Birthday. Issue 5 (4th December 2019) - Anand, Robbyn; Baker, Lane A.; Sun, Li; Zamborini, Francis P.; Zhan, Wei
Abstract : Celebrate in style : This collection honors Dick's scientific contributions in electrochemistry, analytical chemistry, and materials chemistry, as well as three decades of relentless commitment to students and impact on colleagues and the larger scientific community.